2004
DOI: 10.1007/bf03346251
|View full text |Cite
|
Sign up to set email alerts
|

Platelet cGMP inversely correlates with age in healthy subjects

Abstract: Biochemical modifications associated with the increase in platelet activity with age are not well defined. Furthermore it is well known that the nitric oxide/cyclic 3', 5'-guanosine monophosphate (cGMP) pathway regulates platelet aggregation. The aim of the present study was to examine the relationship between platelet content of cGMP and age. 120 normal subjects, evaluating the cGMP platelet concentration, 17betaE2, IGF-I, dehydroepiandrosterone sulphate (DHEAS), insulin, plasma glucose, lipid pattern, homocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 53 Little is known about platelet NO responsiveness and age in unselected subjects, other than the phenomenon of age‐related reduction in platelet cGMP. 54 These parameters have not been assessed simultaneously in the past nor have they been followed up in the same cohort. Thus, the novelty of the current study is that it longitudinally evaluated changes in platelet aggregability, NO responsiveness, arterial stiffness, and ADMA concentrations in the same cohort of aging, but otherwise unselected, subjects and correlated these with one another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 Little is known about platelet NO responsiveness and age in unselected subjects, other than the phenomenon of age‐related reduction in platelet cGMP. 54 These parameters have not been assessed simultaneously in the past nor have they been followed up in the same cohort. Thus, the novelty of the current study is that it longitudinally evaluated changes in platelet aggregability, NO responsiveness, arterial stiffness, and ADMA concentrations in the same cohort of aging, but otherwise unselected, subjects and correlated these with one another.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a relationship between age and ADMA concentrations as well as between age and platelet hyperaggregability . Little is known about platelet NO responsiveness and age in unselected subjects, other than the phenomenon of age‐related reduction in platelet cGMP . These parameters have not been assessed simultaneously in the past nor have they been followed up in the same cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Across studies in the elderly population, there is an increased concentration of clotting factors and a reduction in fibrinolytic activity in elderly populations [89,90]. Other factors that are reported to be altered with aging include: increased platelet aggregability, decreased concentration of cGMP, asymmetric phospholipid structure, reduced membrane potential of mitochondria, elevated concentrations of immunoglobulin G and fibrinogen, and impaired reactivity of platelets to thrombin [91][92][93][94]. In elderly populations, the concomitant presence of atherosclerosis complicates the distinction between age-related or vascular disease-associated changes in platelets and the clotting cascade.…”
Section: Adenosine Receptors and Platelets During Agingmentioning
confidence: 99%
“…On the other hand, NO actions are likely to be mediated by the activation of soluble guanylate cyclase that, in turn, is followed by increase in cGMP production 25 . Accordingly, we have previously demonstrated in vivo that serum DHEA‐S levels positively correlate with platelet cGMP in humans 26 …”
Section: Introductionmentioning
confidence: 95%
“…25 Accordingly, we have previously demonstrated in vivo that serum DHEA-S levels positively correlate with platelet cGMP in humans. 26 Based on the foregoing, aim of the present study was to verify whether short-term treatment with DHEA is able to positively affect platelet cGMP levels, as a marker of NO production, in male aged subjects, who are characterized by low circulating levels of DHEA-S. To this goal, in a placebo-controlled study, platelet cGMP levels as well as serum levels of DHEA, DHEA-S, IGF-1, insulin, glucose, 17 β -oestradiol (E 2 ), testosterone, PAI-1 antigen (PAI-1 Ag), homocysteine and lipid profile were evaluated before and during the administration of placebo or DHEA at physiological doses. 27…”
Section: Introductionmentioning
confidence: 99%